Immunostaining characteristics of irisin in benign and malignant renal cancers - Kuloglu, T.; Artas, G.; Yardim, M.; Sahin, I; Aydin, Y.; Beyoglu, N.; Aydin, S. (Taylor & Francis Ltd, 2019)
We investigated the expression of irisin in renal cancers using immunocytochemistry. Irisin has been reported to exhibit anticancer properties. The study groups consisted of 22 cases each of control renal tissue, oncocytoma, chromophobe renal cell carcinoma (RCC), clear cell RCC (Fuhrman nuclear grades 1, 2, 3 and 4) and papillary RCC. We evaluated 10 slides for each of 176 cases. Slides were immunostained for irisin and histoscores were calculated for the prevalence and strength of immunostaining. Fuhrman nuclear grade 1, 2, 3 clear cell RCC and papillary RCC exhibited no irisin immunoreactivity. Irisin immunoreactivity was observed in some Fuhrman nuclear grade 4 RCCs. We found a significant decrease in irisin staining in chromophobe RCC compared to the control. Immunoreactivity in the oncocytoma tissue was comparable to the control group. Irisin immunoreactivity in chromophobe RCC decreased and no immunoreactivity was observed in Fuhrman nuclear grade 1, 2, 3 clear cell RCC and papillary RCC. Immunistochemical screening of irisin in renal oncocytomas and renal cancers may be useful for differential diagnosis.
Keywords: Cancer; chromophobe RCC; clear cell RCC; Fuhrman nuclear grade; irisin; oncocytoma; renal tissue